2014
DOI: 10.1017/s0305000913000585
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and language on co-speech gesture production: an investigation of French, American, and Italian children's narratives

Abstract: The aim of this paper is to compare speech and co-speech gestures observed during a narrative retelling task in five- and ten-year-old children from three different linguistic groups, French, American, and Italian, in order to better understand the role of age and language in the development of multimodal monologue discourse abilities. We asked 98 five- and ten-year-old children to narrate a short, wordless cartoon. Results showed a common developmental trend as well as linguistic and gesture differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
60
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 42 publications
9
60
0
8
Order By: Relevance
“…Our second finding is in line with the gesture-speech parallel development view (Colletta et al, 2015;Gullberg & Narasimhan, 2010;Nicoladis, 2002). This is in contrast with the tradeoff view (Acredolo & Goodwyn, 1988;Church & Goldin-Meadow, 1986;Iverson & Goldin-Meadow, 2005;Kidd & Holler, 2009).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our second finding is in line with the gesture-speech parallel development view (Colletta et al, 2015;Gullberg & Narasimhan, 2010;Nicoladis, 2002). This is in contrast with the tradeoff view (Acredolo & Goodwyn, 1988;Church & Goldin-Meadow, 1986;Iverson & Goldin-Meadow, 2005;Kidd & Holler, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, children and adults who used the two verbs to distinguish object positions produced gestures depicting the objects (as well as movement path). Finally, Colletta et al (2015) compared speech and gesture produced in a narrative task in 5-and 10-year-old French-, American-, and Italian-speaking children. The authors found that as the children became able to deliver longer and more detailed accounts of a story, they increased the use of co-speech gestures to represent and track the characters in the story.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caselli, Rinaldi, Stefanini and Volterra (2012), studying children aged 0;8 to 1;6, found that it is after 1;4 that word production exceeds gesture production in children's communicative repertories. Gestures and speech remain strongly associated throughout the language development process, and the gesturalvocal system evolves, fulfilling new specific functions in later language learning (Colletta, Guidetti, Capirci, Cristilli, Demir, Kunene-Nicolas & Levine, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Literature on the communicative behaviour of young children from a multimodal perspective is steadily growing, for instance, for French (Colletta, 2004;Colletta et al, 2015;Guidetti, 2002, for Italian (Graziano, 2009 to name a few. However, little is known about how multimodal speech develops after two years.…”
Section: Introductionmentioning
confidence: 99%